Autoantibodies against tyrosyl-tRNA synthetase and its separated domains at essential hypertension - Grom, M.Yu.; Yakovenko, L.F.; Granich, V.M.; Dobrohod, A.S.; Torbas, O.O.; Radchenko, A.D.; Sirenko, Yu.M.; Sidorik, L.L.; Kornelyuk, A.I. (Вiopolymers and Cell, 2015)
In addition to the key role in biosynthesis some aminoacyl-tRNA synthetases provide non-canonical functions. Particularly, separated fragments of tyrosyl-tRNA synthetase (TyrRS) involved into angiogenesis and inflammation. Meanwhile, the vascular inflammation and endothelial dysfunction are central characteristics of the pathogenesis of essential hypertension (EH). The latest studies highlight a role of antibodies in physiopathology of EH. Aim. We had investigated the full-length TyrRS and its domains as autoantigens in sera of the persons with EH (n = 25), the healthy individuals with family history of the pathology (n = 12), and in the control group of healthy subjects (n = 32). Methods. The recombinant TyrRS and its separated domains coupled with His-tags and generated by Escherichia coli were purified by chromatography on Ni-NTA-agarose. The levels of specific autoantibodies (aAbs) in sera of volunteers were measured by ELISA and confirmed in an immunoblotting assay. Results. Some subjects with elevated levels of aAbs against the full-length enzyme were detected in the cohort studies. 52 % of the persons with EH as immunoreactive against miniTyrRS (p < < 0.001) and 50 % against CTD (p = 0.002) were identified. In 50 % of the healthy individuals with family history of EH (p = 0.037) the levels of anti-CTD aAbs were elevated. Conclusions.The increased levels of aAbs against miniTyrRS and CTD in sera of the persons with EH potentially may be used as a prognostic marker of the disease severity or therapy effectiveness. Moreover, the immunoreactivity of healthy individuals with family history of EH against CTD may be an early marker of hypertension.